2022
DOI: 10.1111/jfpp.16331
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approach to investigate the effect of vibro‐fluidized bed drying on bioactive compounds of muskmelon ( Cucumis melo ) seeds

Abstract: Muskmelon seeds hold tremendous potential to be utilized as a source of bioactive compounds as these seeds are discarded as waste during melon processing. Hence, the present study aims to optimize the process parameters of a vibro-fluidized bed drying i.e., temperature (40-60°C), vibration strength (0.55-1.23), and air velocity (7-11 m/s) on bioactive compound of muskmelon seeds. Maximum retention total phenolic content (977.56 mg GAE/100 g), total antioxidant activity (47.84% DPPH reduction), oil yield (50.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Te microwave pretreatment conditions and hot air drying temperatures were based on preliminary experimental results, our previous studies [13,22], and important similar studies on drying of fruits and vegetables reported in the literature [20,21,29,30,32,35,36]. 90 W was chosen as the efective microwave power to obtain the best drying characteristics of orange slices without causing any burning of the products.…”
Section: Drying Processesmentioning
confidence: 99%
“…Te microwave pretreatment conditions and hot air drying temperatures were based on preliminary experimental results, our previous studies [13,22], and important similar studies on drying of fruits and vegetables reported in the literature [20,21,29,30,32,35,36]. 90 W was chosen as the efective microwave power to obtain the best drying characteristics of orange slices without causing any burning of the products.…”
Section: Drying Processesmentioning
confidence: 99%
“…The optimization of the process of drying melon seeds in a vibrofluidized bed confirmed that the intervention of vibration in the fluidization process can lead to the production of high-quality dried seeds. A fluidized bed vibratory dryer can be implemented as an alternative drying method to reduce drying time, processing costs, and ensure better product quality [16]. There are still unresolved issues related to the pressing of oil from melon seeds.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%